Effect of Transparency, Accountability and Community Participation on Village Fund Management in Mamasa Regency - Nuramal, Nuramal; Rusni, Rusni; Ishak , Ishak; Abduh, Muahammad (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This article explores the effect of Transparency, Accountability and Community Participation on Village Fund Management. The objective is to analyze the partial effect of the independent variables on the dependent variable. Transparency, Accountability and Community Participation are independent variables, while Village Fund Management is the dependent variable. The research was carried out in Mamasa Regency. The research respondents were 51 people selected by purposive sampling technique. The research data were obtained through questionnaire distribution. Multiple regression analysis was used to analyze the data. The results are then interpreted. The conclusion was drawn that Transparency and Accountability have significant and partial effect on Village Fund Management. Meanwhile, Community Participation has no effect on Village Fund. Thus, Transparency and Accountability need to be considered by the village level government in Bambang Sub-district, Mamasa Regenc, who manages the village funds so that the objectives of providing funding assistance for village development can be achieved.